Phytochemical Screening and Antidiabetic, Antihyperlipidemic, and Antioxidant Properties of Anthyllis henoniana (Coss.) Flowers Extracts in an Alloxan-Induced Rats Model of Diabetes. (24th June 2018) - Ben Younes, Ameur; Ben Salem, Maryem; El Abed, Hanen; Jarraya, Raoudha
Abstract : Background . This study investigates the biological activities of Anthyllis henoniana flowers extracts. Materials and Methods . Antioxidant activity and the in vitro inhibitory effect of key digesting enzymes related to postprandial hyperglycemia were determined. Diabetic rats were orally and daily given the best extract from flowers of Anthyllis henoniana at a dose of acarbose for one month. Results . Among the extracts, the ethyl acetate one displayed remarkable antioxidant activity including DPPH (IC50 = 2.34 mg/mL) and was more effective in inhibiting α -glucosidase (IC50 = 17 μ g/mL) than α -amylase (IC50 = 920 μ g /mL) activities. In vivo, the results proved that ethyl acetate extract at doses of 400 mg/kg bw decreased significantly the blood glucose level and lipid profile levels and increased the activities of antioxidant enzymes. These protective impacts of Anthyllis henoniana ethyl acetate flowers extract were confirmed by histological results. Conclusion . This study demonstrates, for the first time, that Anthyllis henoniana flowers ethyl acetate extract is effective in inhibiting hyperglycemia and oxidative stress caused by diabetes.